2021
DOI: 10.3390/polym13193393
|View full text |Cite
|
Sign up to set email alerts
|

Boron Nitride-Filled Linear Low-Density Polyethylene for Enhanced Thermal Transport: Continuous Extrusion of Micro-Textured Films

Abstract: With shrinking size of electronic devices, increasing performance and accompanying heat dissipation, there is a need for efficient removal of this heat through packaging materials. Polymer materials are attractive packaging materials given their low density and electrical insulating properties, but they lack sufficient thermal conductivity that inhibits heat transfer rate. Hexagonal boron nitride (BN) possesses excellent thermal conductivity and is also electrically insulating, therefore BN-filled polymer comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 41 publications
1
7
0
Order By: Relevance
“…This change can be associated with the geometrical advantages of BNNT and its relative effective dispersion, and the surface treatment compatibility with the polymeric composite. This stipulates the relative contribution of BNNT on the thermal composite material [25]. The structural attributes and elemental characteristics of BNNT before and after modification are presented in Figures 2d-g and S1a-d through TEM images and TEM-EDX.…”
Section: Chemical and Physical Characterization Of Bnnt-capamentioning
confidence: 80%
See 1 more Smart Citation
“…This change can be associated with the geometrical advantages of BNNT and its relative effective dispersion, and the surface treatment compatibility with the polymeric composite. This stipulates the relative contribution of BNNT on the thermal composite material [25]. The structural attributes and elemental characteristics of BNNT before and after modification are presented in Figures 2d-g and S1a-d through TEM images and TEM-EDX.…”
Section: Chemical and Physical Characterization Of Bnnt-capamentioning
confidence: 80%
“…This change can be associated with the geometrical advantages of BNNT and its relative effective dispersion, and the surface treatment compatibility with the polymeric composite. This stipulates the relative contribution of BNNT on the thermal composite material [25].…”
Section: Chemical and Physical Characterization Of Bnnt-capamentioning
confidence: 99%
“…), graphite, carbon fibers, carbon nanotubes, and ceramic particles (Al 2 O 3 , SiC, and BN) have been incorporated into the polymer matrix to enhance various customized properties, such as heat resistance, thermal conductivity, and mechanical properties. [52][53][54][55][56] Micro/nanolayer coextrusion based on layer multiplication has recently attracted considerable interest in the polymer industry. [57] This novel polymer processing technology can be used to manufacture films consisting of hundreds of layers with thicknesses less than 100 nm, which can be applied in light-reflective films, optical lenses, and soundproofing film/foam multilayered composites.…”
Section: Microextrusion Moldingmentioning
confidence: 99%
“…Wei et al 16 prepared thermal conductive phase-change materials (PCMs) composed of poly(ethylene glycol) (PEG) and BN, whose TC was 2.86 times that of neat PEG. Guzdemir et al 17 studied BN-filled polymer composites and found that 30 vol % BN led to an increment of 500% in TC as compared with neat polymer.…”
Section: Introductionmentioning
confidence: 99%